Bisphenol A release from an orthodontic resin composite: A GC/MS and LC/MS study. Issue 2 (February 2018) - Deviot, Marc; Lachaise, Isabelle; Högg, Christof; Durner, Jürgen; Reichl, Franz-Xaver; Attal, Jean-Pierre; Dursun, Elisabeth
Abstract: Objectives: First, to analyse the in vitro release of BPA and Bis-GMA from an orthodontic resin composite (Transbond XT, 3M Unitek), stored in various conditions, by gas chromatography/mass spectrometry (GC/MS) and liquid chromatography/mass spectrometry (LC/MS); then to extrapolate the data to the clinical situation. Secondly, to explore the thermal stability of Bis-GMA. Methods: Cylinders of resin composite were prepared and stored according to 3 different protocols: (1) they were light-cured 20 s, then placed in artificial saliva; (2) they were light-cured 2 s, then placed in acetonitrile; (3) they were light-cured 2 s, then placed in methanol. For each group, BPA and Bis-GMA release were determined with GC/MS and/or LC/MS at least after one week. Besides, 120 brackets (10 of each type) were bonded over metal teeth, then debonded, and the weight and the surface of resin composite residues were measured. BPA and Bis-GMA release of adhesive residues were extrapolated from the data obtained with the cylinders. Besides, BPA release from a heated Bis-GMA solution was measured. Results: With GC/MC, BPA was detected in all samples. With LC/MS, BPA was detected only from samples immersed in MeOH; Bis-GMA was detected, in varying amount according to the extraction media and the light-curing time. BPA was found after heating of the Bis-GMA solution. Significance: Contamination risk and the heat applied in GC/MS may overestimate the BPA release from resin composite. Based on the LC/MS results, the risk of BPA release after orthodontic bonding would be more than 42 000 times lower than the TDI for a 30-kg child.